Assessment of surface water quality in a Malaysian Port via multivariate statistical analysis / Wan Nur Fazlina Abdol Jani ... [et al.] - Abdol Jani, Wan Nur Fazlina; M.H, Firdaus; Suja, Fatihah; Md Zain, Shahrom; Abdullah, M. (Universiti Teknologi MARA, Perak, 2022)
Maritime transport has become an important method of comprehensive connectivity for imports and exports for major centers of economic activity all over the world. However, transport and port activities have grown without addressing their pollution impact on the environment. Marine water samples in a port in Malaysia were collected to find the similarities and differences in the physicochemical aspect. The principal component analysis concluded that 87.0% of the variance was explained by the four components at high tide, each accounted for 33.6% (physicochemical), 26.9% (correlation between pH and organic matter), 14.1% (trace metals), and 12.4% of the total variance (the concentration of Copper). Then, 94.5% of the total variance of the five components contributed 37.9% (turbidity, pH, organic parameters, and suspended solids), 19.6% (parameter Zn), 17.4% (parameter Ni), 11.7% (average of organic pollutants) and 7.7% of the total variance (DO and physical factors associated with TSS), each at low tide have been identified. Hierarchical cluster analysis grouped eight sampling stations into four clusters of similar water quality characteristics at both tides. Therefore, water quality monitoring and the control of untreated metal and organic waste discharge into marine waters are indispensable.